Injuries in youth football and the relationship to player maturation: An analysis of time-loss injuries during four seasons in an English elite male football academy - Light, N.; Johnson, A.; Williams, S.; Smith, N.; Hale, B.; Thorborg, K. (Scandinavian Journal of Medicine & Science in Sports, 2021)
A better insight into injuries in elite-youth football may inform prevention strategies. The purpose of this prospective cohort study was to investigate the frequency, incidence, and pattern of time-loss injuries in an elite male football academy, exploring injuries in relation to age and maturation status. Across four consecutive playing seasons, playing exposure and injuries to all academy players (U`9 to U`21) were recorded by club medical staff. Maturation status at the time of injury was also calculated for players competing in U`13 to U`16 aged squads. Time-loss injury occurrence and maturation status at time of injury were the main outcome measures. A total of 603 time-loss injuries were recorded, from 190 different players. Playing exposure was 229 317 hours resulting in an overall injury rate of 2.4 p/1000 h, ranging from 0.7 p/1000 h (U`11) to 4.8 p/1000 h (U`21). Most injuries were traumatic in mechanism (73%). The most common injury location was the thigh (23%), and the most common injury type was muscle injury (29%) combining to provide the most common injury diagnosis; thigh muscle injury (17%). In U`13-U`16 players, a higher number of injuries to early-maturing players were observed in U`13-U`14 players, while more injuries to U`15-U`16 players occurred when classed as "on-time" in maturity status. Maturation status did not statistically relate to injury pattern; however, knee bone (not-fracture) injuries peaked in U`13 players while hip/groin muscle injuries peaked in U`15 players.